Abrasive/Erosive Wear on MMCs in Plastic Molds as a Function of Volumetric Flow Rates and Glass Fiber Distribution. (22nd November 2018) - Blutmager, Andreas; Varga, Markus; Schmidt, Tobias; Pock, Alexander; Friesenbichler, Walter
Abstract : In injection molding wear of components is pronounced in positions with high flow rates of melt. The platelet‐wear‐test is an established method for comparative assessment of wear resistance of tool materials in such regimes. Within this study three metal matrix composites: two hard metals and one powder metallurgical steel were investigated. Results show non‐linear wear rates with increasing amount of plastic melt processed. The reasons were found in the viscous dissipation, which is based on high volumetric flow rates and the small wear gap, leading to a temperature rise, which are detrimental especially for the PM‐steel. Analysis of the processed glass fiber‐filled polymer showed dramatic decrease of fiber length due to the processing through the wear gap. This entails a high amount of free fiber ends, resulting in higher load for the surfaces through micro chipping. POLYM. ENG. SCI., 59:E302–E311, 2019. © 2018 The Authors. Polymer Engineering & Science published by Wiley Periodicals, Inc. on behalf of Society of Plastics Engineers.